SEDIMENT ACCUMULATION PROFILE IN MANGROVE RESTORATION AREA OF LEMBAR BAY-LOMBOK ISLAND - Mohammad Sumiran Paputungan; Alan Frendy Koropitan; Tri Prartono; Ali Arman Lubis (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Mangrove restoration is really needed for restoring its ecosystem functions, so that it could be able to support fisheries activity and to protect coastal by extreme weather. In addition, mangrove is able to accumulate sediment that important in protecting the coastal area from sea level rise. Therefore, the aim of this study is to investigate sediment accumulation rate in mangrove area during post restoration. Sampling location were divided into three different stations based on estimated restoration ages, such as ≥ 15 years old (Station 1), 4 - 10 years old (Station 2) and 2 - 8 years old (Station 3). Sediment cores were carried out by inserting 7.6 cm diameter and 100 cm length of polyvinyl chloride pipes. Sedimentation rate is measured by using Pb-210 radionuclide analysis. The results show that the sediment accumulation rate in the last 20th years from all station ranges from 0.17 to 0.42 g/cm2/year. The highest accumulation rate is found at oldest year old station while the lowest accumulation rate is found at younger year old station of mangrove restoration area. Restoration process is clearly able to recover the mangrove’s role in trapping sediment in coastal region. Keywords: sediment accumulation, mangrove restoration, Lembar Bay- Lombok Island